2015
DOI: 10.3390/molecules20045987
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Start Codon Targeted (SCoT) Markers to Estimate Genetic Diversity and Relationships among Chinese Elymus sibiricus Accessions

Abstract: Elymus sibiricus as an important forage grass and gene pool for improving cereal crops, that is widely distributed in West and North China. Information on its genetic diversity and relationships is limited but necessary for germplasm collection, conservation and future breeding. Start Codon Targeted (SCoT) markers were used for studying the genetic diversity and relationships among 53 E. sibiricus accessions from its primary distribution area in China. A total of 173 bands were generated from 16 SCoT primers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 35 publications
(51 reference statements)
2
24
2
Order By: Relevance
“…Evaluation of SCoT markers has Fig. 4 The dendrogram of the six examined soybean cultivars as constructed using protein patterns unweighted pair-group arithmetic (UPGMA) and similarity matrices computed according to Jaccardʼ coefficient already been established in Elymus sibiricus and Vigna unguiculata (Zhang et al, 2015;Igwe et al, 2017), respectively. In the present study, there is no linkage between GC content of primer and the clarification of the banding profile was reported which is in harmony with Marilla and Scoles (1996).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of SCoT markers has Fig. 4 The dendrogram of the six examined soybean cultivars as constructed using protein patterns unweighted pair-group arithmetic (UPGMA) and similarity matrices computed according to Jaccardʼ coefficient already been established in Elymus sibiricus and Vigna unguiculata (Zhang et al, 2015;Igwe et al, 2017), respectively. In the present study, there is no linkage between GC content of primer and the clarification of the banding profile was reported which is in harmony with Marilla and Scoles (1996).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the EST-SSR markers developed in this study had a higher level of polymorphism compared with the genomic SSR markers reported by Lei et al 4 . Furthermore, a series of achievements on the genetic diversity of wild E. sibiricus germplasm and populations were reported 3 19 53 54 , and these showed a clear demarcation between accessions from different regions. However, the dendrogram of 15 E .…”
Section: Discussionmentioning
confidence: 99%
“…In total, 273 polymorphic bands were detected with an average of 11.4 bands per primer. In the study ZHANG et al (2015) used SCoT markers to study the genetic diversity and relationships among 53 Elymus sibiricus accessions. KHAN et al (2016) studied genetic differences to evaluate the level and distribution of diversity among genotypes of Mentha using SCoT markers.…”
Section: Resultsmentioning
confidence: 99%